Dampak Distraksi Audiovisual Terhadap Distress Anak Yang Mendapatkan Terapi Inhalasi - Riau Roslita Roslita; Nani Nurhaeni; Dessie Wanda (STIKes Hang Tuah Pekanbaru, 2021)
Inhalation therapy as one of the management of children with respiratory system disorders often causes distress, especially in young children. Distress when administering inhaled therapy may decrease the effectiveness of the given treatment. The goal of this innovation project is to identify the effectiveness of audiovisual distraction on distress in children with respiratory system disorders and inhalation therapy. This innovation project method used PICO. The sample was 15 people consisting of 8 controls and 7 intervention groups. The results of the innovation project showed a significant difference between the children's distress score in the control group and the intervention (p = 0.001). Conclusions: Audiovisual distraction interventions are expected to be applied to children with oxygen distress disorder during inhalation therapy.